Analisis Minat Dan Motivasi Dalam Penulisan Karya Ilmiah Pada Mahasiswa Program Studi Pendidikan Matematika Universitas Flores - Maria Waldetrudis Lidi; Ningsih (Program Studi Pendidikan Ekonomi, Universitas Flores, 2018)
One effort to improve the education is by doing research because it can improve someone competence which is found by the motivation and needs in developing a scientific writing. This research is a descriptive qualitative. Subject of this research is analyzing the students’ needs and motivation in mathematics study program toward ability to write a scientific writing for academic years 2015/2016 with involved 109 students in semester II to semester VI randomly. This research was conducted at Mei-June 2016. Data collection was taken by giving the questionaire. Due to the result of the analysis, and discussion so that it can conclude that students’ need to write the scientic writing 70% is categorized strong, meanwhile intrinsinc motivation is strongest than extrinsic motivation. It can show by the data of students’ extrinsinc motivation is 55%, meanwhile intrinsic motivation is strongest is about 92%.